The Incidence of Sales Taxes: Rejoinder - Gilbert, D. W. (Quarterly Journal of Economics, 1940)
Journal Article The Incidence of Sales Taxes: Rejoinder Get access Donald W. Gilbert Donald W. Gilbert University of Rochester Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 4_Part_1, August 1940, Pages 686–693, https://doi.org/10.1093/qje/54.4_Part_1.686 Published: 01 August 1940